374 Are Operative Notes Adhering to the Standards of Good Practice?. (28th February 2022) - Lipski, C.; Bleibeh, S.; Hanif, U.; Sinha, M.; Waites, M.
Abstract: Aim: Thorough documentation is imperative for postoperative care, quality improvement, research, and medico-legal enquiries. For these reasons this closed loop audit aimed to assess whether the local Trauma and Orthopaedic departments' operative notes were adhering to the guidance outlined by The Royal College of Surgeons, in order to to follow good practice. Method: This was a random data collection, single centre study performed which analysed 50 operative notes from a variety of Trauma and Orthopaedic surgical procedures (not including neck of femur fractures and elective surgeries). The next cycle of the audit was completed after departmental re-education and a new operative note pro forma was created and put in place. Results: The first audit cycle demonstrated that 8 categories in the operative note were below 96 % compliance with the guidance, of these being: time, name of operating surgeon/anaesthetist, operative procedure, incision, operative diagnosis, DVT prophylaxis, signature. Furthermore, an interesting finding showed no complications were identified in any operative note, similarly no extra procedures were documented. The second audit cycle showed that there was 100% compliance gained across all categories. Additionally, the new pro forma had an option to specify if there was/or not any complications, which had 100 % compliance in the second cycle and identified one complication. Conclusions: Overall this audit was able to standardise the operative notes and improve quality and structure in order to follow good practice, by implementing a new pro forma and re-educating the department. This ensures that the best standard of care is being delivered.